ELIMINATING NEGATIVE ATTITUDE TOWARDS READING BY MUTUAL ACTION OF OTHER ARTS - Павле Ј. Илић (Faculty of Philosophy, University of Novi Sad, City Library of Pančevo, 2010)
Nowadays pupils more often avoid reading set books and other texts during literature teaching and a lot of factors have contributed to this situation (a large curriculum, inadequate and oldfashioned teachers' attitude towards both teaching materials and pupils, and visual media attractiveness). The ways of eliminating the negative attitude towards reading should follow new trends and be in correlation of art disciplines.